Patients′ attitude towards medical students rotating in the dermatology clinic - Bukhari Iqbal; AlAkloby Omar; Al Saeed Wafa (Wolters Kluwer Medknow Publications, 2008)
Objective: To study the attitudes of the patients towards medical students rotating in the dermatology clinic in the King Fahad Hospital of the University (KFHU). Materials and Methods: One hundred and two adult outpatients attending the KFHU in Alkhobar, Saudi Arabia during the period March to June 2004 completed a questionnaire to evaluate their receptiveness towards medical students attending with the dermatologist. Results: Almost 57% preferred physician and medical student participation in their care and 46% welcomed their presence during physical examination. The majority of patients (64.8%) felt comfortable disclosing personal information to the medical student and (68.7%) enjoyed the interaction with the medical students. Patients (63.7%) agreed that the students understood their healthcare needs. Conclusion: The majority of the patients in this study enjoyed their interactions with the students and felt comfortable disclosing information. Some patients want to spend time alone with the physician so permission for medical student participation should be requested.